Elaboration of Science Self-Learning Modules from the Perspective of Instructional Design: A Pilot Study - Llona-Rodriguez, I (American Scientific Publishers, 2017)
Instructional design is an integrated lesson planning that incorporates the different inter-dependent elements involved in the teaching-learning process. The objective of this article is to provide an updated view on how the main elements of instructional design can be considered when elaborating self-learning modules based on this approach. In addition, the article includes the results of pilot study using a self-learning module on “action potential” for bio-medical students which, in general, showed an improvement in the academic results after using this supporting teaching resource. Developing self-leaning materials following the guidelines of instructional design may be replicated for other topics included in physiology courses as well as other disciplines, and could be useful for bio-medical students to learn more effectively. © 2017 American Scientific Publishers All rights reserved.